Effect of Laser Irradiation on Cell Cycle and Mitosis - Ganjali, Monireh; M. Seifalian, Alexander; Mozafari, Masoud (Journal of Lasers in Medical Sciences, 2018)
Introduction: In this research, low-level helium-neon (He-Ne) laser irradiation effects on monkey kidney cells (Vero cell line) mitosis were studied. Methods: The experiment was carried out on a monkey kidney cell line “Vero (CCL-81)”. This is a lineage of cells used in cell cultures and can be used for efficacy and media testing. The monolayer cells were formed on coating glass in a spectral cuvette (20×20×30 mm). The samples divided into two groups. The first groups as irradiated monolayer cells were exposed by a He-Ne laser (PolyaronNPO, L’vov, Ukraine) with λ = 632.8 nm, max power density (P) = 10 mW/cm2, generating linearly polarized and the second groups as the control monolayer cells were located in a cuvette protected by a lightproof screen from the first cuvette and also from the laser exposure. Then, changing functional activity of the monolayer cells, due to the radiation influence on some physical factors were measured. Results: The results showed that low-intensity laser irradiation in the range of visible red could make meaningful changes in the cell division process (the mitosis activity). These changes depend on the power density, exposure time, the presence of a magnetic field, and the duration of time after exposure termination. The stimulatory effects on the cell division within the power density of 1-6 mW/(cm2) and exposure time in the range of 1-10 minutes was studied. It is demonstrated that the increase in these parameters (power density and exposure time) leads to destructing the cell division process. Conclusion: The results are useful to identify the molecular mechanisms caused by low-intensity laser effects on the biological activities of the cells. Thus, this study helps to optimize medical laser technology as well as achieving information on the therapeutic effects of low-intensity lasers.